A new species of Anacaena Thomson, 1859 from South Africa (Coleoptera: Hydrophilidae) - Bilton, David T.; Komarek, Albrecht (Zootaxa, 2016)
Anacaena namaqua sp. nov. is described from the Northern Cape and Western Cape provinces of South Africa, in an area transitional between the fynbos and succulent karoo biomes. The habitus, aedeagus, femoral pubescence and habitats of the new species are illustrated, together with details of its ecology. A key to all Anacaena confirmed from South Africa to date is also provided.